Method for realizing brazing of dissimilar materials based on hollow glass bead composite brazing filler metal

By using hollow glass microbead composite brazing, the problems of low joint strength and enhanced phase agglomeration caused by the difference in thermal expansion coefficient in different materials are solved, and the high-temperature mechanical properties and shear strength are improved, which significantly improves brazing Stability and strength of the joint.

CN119260244AActive Publication Date: 2025-01-07HARBIN INST OF TECH

Patent Information

Application Number
CN202411608523.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-07
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

During the brazing process of different materials, due to the large difference in thermal expansion coefficient, the strength of the brazed joint is low, and the addition of enhanced phase particles to the brazing joint is prone to agglomeration, which affects the stability of the mechanical properties of the joint.

Method used

Using hollow glass microbead composite solder, the hollow glass microbeads are mixed with the solder powder, ultrasonic cleaning and vacuum drying are carried out to form the dried hollow glass microbead composite solder, and the soldering connection is carried out under vacuum conditions. , the low thermal expansion coefficient and spherical structure of hollow glass microbeads are used to reduce the thermal expansion coefficient and brittle compound generation of the brazing joints.

Benefits of technology

The residual stress of the brazed joint is significantly reduced, the high-temperature mechanical properties and shear strength of the joint are improved, and the enhanced phase agglomeration is avoided, and the brazed joint with excellent performance is obtained. The stress distribution is improved through the porous structure and the brazed joint performance is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119260244A_ABST
    Figure CN119260244A_ABST
Patent Text Reader

Abstract

The invention discloses a method for achieving dissimilar material brazing based on hollow glass bead composite brazing filler metal, and relates to the technical field of dissimilar material brazing. The problems that in the brazing process of traditional dissimilar materials and between base metal and brazing filler metal, due to the fact that the difference of thermal expansion coefficients is large, the strength of a brazed joint is low, reinforced phase particles are added into brazing seams to relieve residual stress, the reinforced phase particles are prone to agglomeration, and the stability of the mechanical property of the joint is affected are solved. The hollow glass beads in the hollow glass bead composite brazing filler metal have low specific surface area, and agglomeration of a reinforced phase in the brazing process is effectively avoided; meanwhile, the hollow glass beads are well combined with the brazing filler metal, defects such as holes do not exist, the spherical structures of the glass beads are well reserved, the coefficient of thermal expansion of brazing seams is remarkably reduced, residual stress generated by a joint during brazing is relieved, and a brazing joint with excellent performance is obtained. The method for achieving dissimilar material brazing based on the hollow glass bead composite brazing filler metal can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of brazing of dissimilar materials, and in particular to a method for brazing dissimilar materials based on hollow glass microsphere composite brazing material. Background Art

[0002] The connection of dissimilar materials to form composite components can maximize the excellent properties of each material and meet the functional and performance requirements of modern engineering structures. Compared with other welding methods, brazing is one of the most effective methods to achieve the connection of dissimilar materials such as metals, ceramics, composite materials and glass. However, the large difference in thermal expansion coefficients between dissimilar materials and between the base material and the brazing material makes it very easy for the joint to produce large residual stress, which seriously weakens the strength of the brazed joint and even directly leads to cracking after welding. In addition, a large amount of brittle compounds are easily generated in the brazing seam, which also affects the mechanical properties of the joint.

[0003] At present, the most common method to relieve residual stress is to use composite solder. Composite solder refers to adding a reinforcement phase with a low thermal expansion coefficient to a traditional metal solder to reduce the thermal expansion coefficient of the solder, thereby relieving the residual stress caused by the mismatch of thermal expansion coefficients. Adding nano-Al2O3, TiO2, CNTs and other reinforcement phase particles with low thermal expansion coefficients to the solder will relieve the residual stress of the joint to a certain extent, but when the amount of reinforcement phase added is large, it is easy to agglomerate due to its large surface energy, and the mechanical properties of the joint will be reduced. Therefore, the range of nano-reinforcement phase that can be added is small, and the thermal expansion coefficient of the composite solder is still quite different from that of the base material. The effect of using nano-reinforced phase composite solder to relieve the residual stress of the joint is extremely limited. Summary of the invention

[0004] The purpose of the present invention is to solve the problem that in the traditional brazing process between dissimilar materials and between a base material and a brazing filler metal, the strength of the brazed joint is low due to the large difference in thermal expansion coefficients, and the reinforcing phase particles are easily agglomerated by subsequently adding reinforcing phase particles to the brazing seam to alleviate the residual stress, thereby affecting the stability of the mechanical properties of the joint. A method for brazing dissimilar materials based on a hollow glass microsphere composite brazing filler metal is provided.

[0005] A method for preparing a hollow glass microsphere composite solder is carried out according to the following steps:

[0006] Step S1:

[0007] The hollow glass microspheres are dispersed in deionized water, and ultrasonically cleaned at 20-30° C. After the ultrasonic cleaning, the hollow glass microspheres are allowed to stand to remove the precipitate, and the upper floating matter is taken to obtain the hollow glass microspheres with complete structure;

[0008] Step S2:

[0009] The hollow glass microspheres with complete structures obtained in step S1 are placed in a vacuum drying oven for drying to obtain dried hollow glass microspheres;

[0010] Step S3:

[0011] The dried hollow glass microspheres obtained in step S2 are mixed with solder powder, and then a dispersant is added. After mixing evenly, a hollow glass microsphere composite solder is obtained; the mass ratio of the dried hollow glass microspheres to the solder powder is (0.001-0.05):1.

[0012] The method for brazing dissimilar materials based on hollow glass microsphere composite brazing filler metal is carried out in the following steps:

[0013] The hollow glass microsphere composite solder is placed between the surfaces of two dissimilar base materials to be welded for assembly, and then placed in a brazing furnace under a vacuum degree of 1×10 -4 ~5×10 -3 Pa, the temperature is raised to 20-150°C higher than the melting point of the brazing material, and the brazing connection is performed for 1-60 minutes. After the brazing is completed, it is first cooled to 200-450°C, and then cooled to room temperature, completing the brazing of dissimilar materials based on the hollow glass microsphere composite brazing material;

[0014] The dissimilar base materials to be welded are C / C composite materials, SiO 2f / SiO2 composites, C / SiC composites, multiphase ceramics, oxide ceramics, glass-ceramics, sapphire, Ni-based alloys, Ti alloys, Zr alloys, Nb alloys and two of the Fe-based alloys.

[0015] Beneficial effects of the present invention:

[0016] 1. The hollow glass microspheres in the hollow glass microsphere composite solder of the present invention have a lower specific surface area, which effectively avoids the agglomeration of the reinforcing phase during the brazing process; at the same time, the hollow glass microspheres are well combined with the solder, without defects such as holes, and the spherical structure of the glass microspheres is well preserved, which significantly reduces the thermal expansion coefficient of the brazing seam, is beneficial to alleviate the residual stress generated in the joint during brazing, and obtains a brazing joint with excellent performance.

[0017] 2. The hollow glass microspheres in the hollow glass microsphere composite solder of the present invention are dispersed in the soldering seam, which not only has a certain supporting effect, but also can resist the high-temperature softening phenomenon of the solder, thereby significantly improving the high-temperature mechanical properties of the joint.

[0018] 3. The hollow glass microspheres in the hollow glass microsphere composite solder of the present invention are prone to preferentially react with active elements such as Ti, Zr, Cr, etc. existing in the solder and dissolved from the base material into the brazing seam during the brazing process, which significantly inhibits the formation and agglomeration of brittle intermetallic compounds and ensures the mechanical properties of the brazed joint.

[0019] 4. The present invention adopts hollow glass microsphere composite solder. Compared with the microcrystalline glass and C / C material welded by AgCuInTi brazing, the Ti-Cu brittle phase in the obtained joint interface is significantly reduced, and the shear strength of the welded joint reaches 23MPa, which is 400% higher than that without adding glass microspheres.

[0020] 5. The preparation method of the hollow glass microsphere composite solder of the present invention is simple and low in cost. The hollow glass microspheres have the characteristics of low thermal expansion coefficient and not easy to agglomerate, which is conducive to regulating the interface organization and relieving the residual stress of the joint. In addition, the use of hollow glass microsphere composite solder to connect dissimilar materials will obtain a porous brazing joint, which can improve the stress distribution of the joint, and consume the fracture energy when the crack expands, enhance the brazing joint performance, and improve the joint strength.

[0021] The invention can obtain a method for brazing dissimilar materials based on hollow glass microsphere composite brazing filler metal. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 A process flow chart showing the brazing of dissimilar materials based on hollow glass microsphere composite brazing filler metal of the present invention;

[0023] Figure 2 The interface structure morphology of the hollow glass microsphere composite solder brazing joint in Example 1 is shown;

[0024] Figure 3 The interface structure morphology of the direct brazing joint without using glass microspheres in Comparative Example 1 is shown;

[0025] Figure 4 The interface structure morphology of the hollow glass microsphere composite solder brazing joint in Example 2 is shown. DETAILED DESCRIPTION

[0026] Specific implementation method 1: This implementation method is a method for preparing a hollow glass microsphere composite solder, which is carried out according to the following steps:

[0027] Step S1:

[0028] The hollow glass microspheres are dispersed in deionized water, and ultrasonically cleaned at 20-30° C. After the ultrasonic cleaning, the hollow glass microspheres are allowed to stand to remove the precipitate, and the upper floating matter is taken to obtain the hollow glass microspheres with complete structure;

[0029] Step S2:

[0030] The hollow glass microspheres with complete structures obtained in step S1 are placed in a vacuum drying oven for drying to obtain dried hollow glass microspheres;

[0031] Step S3:

[0032] The dried hollow glass microspheres obtained in step S2 are mixed with solder powder, and then a dispersant is added. After mixing evenly, a hollow glass microsphere composite solder is obtained; the mass ratio of the dried hollow glass microspheres to the solder powder is (0.001-0.05):1.

[0033] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that in step S1, the ratio of the mass of the hollow glass microspheres to the volume of deionized water is (5-15) g: (600-1000) mL, and the diameter of the hollow glass microspheres is 2 μm-100 μm.

[0034] The other steps are the same as those in the first specific implementation.

[0035] Specific implementation method three: The difference between this implementation method and specific implementation method one or two is that the ultrasonic cleaning time in step S1 is 0.5 to 12 hours, and the standing time is 1 hour to 3 hours.

[0036] The other steps are the same as those in the first or second embodiment.

[0037] Specific embodiment 4: The difference between this embodiment and specific embodiments 1 to 3 is that during drying in step S2, the vacuum degree in the vacuum drying oven is 1Pa to 100Pa, the drying temperature is 60 to 100°C, and the drying time is 5 to 12h.

[0038] The other steps are the same as those in Specific Embodiments 1 to 3.

[0039] Specific embodiment 5: The difference between this embodiment and specific embodiments 1 to 4 is that the solder powder described in step S3 is Cu-based solder, Ag-based solder, Ni-based solder, Sn-based solder, Ti-based solder or Zr-based solder.

[0040] The other steps are the same as those in Specific Embodiments 1 to 4.

[0041] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that the dispersant described in step S3 is anhydrous ethanol, acetone, ethylene glycol, cellulose solution or isopropanol.

[0042] The other steps are the same as those in Specific Embodiments 1 to 5.

[0043] Specific implementation method 7: The difference between this implementation method and specific implementation methods 1 to 6 is that in step S3, mechanical stirring is used for mixing, the stirring speed is 10 to 500 r / min, and the stirring time is 1 to 30 min.

[0044] The other steps are the same as those in Specific Embodiments 1 to 6.

[0045] Specific implementation method eight: This implementation method is based on the hollow glass microsphere composite solder to achieve the method of brazing dissimilar materials, and is carried out according to the following steps:

[0046] The hollow glass microsphere composite solder is placed between the surfaces of two dissimilar base materials to be welded for assembly, and then placed in a brazing furnace under a vacuum degree of 1×10 -4 ~5×10 -3 Pa, the temperature is raised to 20-150°C higher than the melting point of the brazing material, and the brazing connection is performed for 1-60 minutes. After the brazing is completed, it is first cooled to 200-450°C, and then cooled to room temperature, completing the brazing of dissimilar materials based on the hollow glass microsphere composite brazing material;

[0047] The dissimilar base materials to be welded are C / C composite materials, SiO 2f / SiO2 composites, C / SiC composites, multiphase ceramics, oxide ceramics, glass-ceramics, sapphire, Ni-based alloys, Ti alloys, Zr alloys, Nb alloys and two of the Fe-based alloys.

[0048] Beneficial effects of this embodiment:

[0049] 1. The hollow glass microspheres in the hollow glass microsphere composite solder of this embodiment have a low specific surface area, which effectively avoids the agglomeration of the reinforcing phase during the brazing process; at the same time, the hollow glass microspheres are well combined with the solder, without defects such as holes, and the spherical structure of the glass microspheres is well preserved, which significantly reduces the thermal expansion coefficient of the brazing seam, helps to alleviate the residual stress generated in the joint during brazing, and obtains a brazed joint with excellent performance.

[0050] 2. The hollow glass microspheres in the hollow glass microsphere composite solder of this embodiment are dispersed in the soldering seam, which not only has a certain supporting effect, but also can resist the high-temperature softening phenomenon of the solder, thereby significantly improving the high-temperature mechanical properties of the joint.

[0051] 3. The hollow glass microspheres in the hollow glass microsphere composite solder of this embodiment are prone to preferentially react with active elements such as Ti, Zr, Cr existing in the solder and dissolved from the base material into the brazing seam during the brazing process, which significantly inhibits the formation and agglomeration of brittle intermetallic compounds and ensures the mechanical properties of the brazed joint.

[0052] 4. This embodiment uses hollow glass microsphere composite solder. Compared with the microcrystalline glass and C / C material welded by AgCuInTi brazing, the Ti-Cu brittle phase in the resulting joint interface is significantly reduced, and the shear strength of the welded joint reaches 23MPa, which is 400% higher than that without adding glass microspheres.

[0053] 5. The preparation method of the hollow glass microsphere composite solder in this embodiment is simple and low in cost. The hollow glass microspheres have the characteristics of low thermal expansion coefficient and not easy to agglomerate, which is conducive to regulating the interface organization and relieving the residual stress of the joint. In addition, the use of hollow glass microsphere composite solder to connect dissimilar materials will obtain a porous brazing joint, which can improve the stress distribution of the joint, and consume the fracture energy when the crack expands, enhance the brazing joint performance, and improve the joint strength.

[0054] Specific embodiment 9: The difference between this embodiment and specific embodiment 8 is that the dissimilar base materials to be welded are microcrystalline glass and C / C composite material.

[0055] The other steps are the same as those in the eighth embodiment.

[0056] Specific implementation method ten: This implementation method is different from specific implementation methods eight or nine in that the heating rate is 1 to 30° C. / min, and the cooling rate is 1 to 50° C. / min.

[0057] The other steps are the same as those in the eighth or ninth embodiment.

[0058] The following examples are used to verify the beneficial effects of the present invention:

[0059] Example 1: A method for brazing dissimilar materials based on hollow glass microsphere composite solder is carried out according to the following steps:

[0060] Step S1:

[0061] 5 g of hollow glass microspheres were dispersed in 1000 mL of deionized water, and ultrasonically cleaned at 25°C for 1 h. After ultrasonic cleaning, the mixture was allowed to stand for 3 h to remove the broken glass microspheres, and the upper floating material was taken to obtain hollow glass microspheres with complete structures.

[0062] The diameter of the hollow glass microspheres is 30 μm;

[0063] Step S2:

[0064] The hollow glass microspheres with complete structures obtained in step S1 are placed in a vacuum drying oven and dried for 10 hours at a vacuum degree of 10 Pa and a temperature of 80° C. to obtain dried hollow glass microspheres;

[0065] Step S3:

[0066] The dried hollow glass microspheres obtained in step S2 are mixed with solder powder, and then anhydrous ethanol is added as a dispersant, and mechanically stirred at a stirring speed of 100 r / min for 20 min to obtain a hollow glass microsphere composite solder (such as Figure 1 shown);

[0067] The mass ratio of the dried hollow glass microspheres to the solder powder is 0.005:1, and the solder powder is AgCuInTi solder;

[0068] Step S4:

[0069] The hollow glass microsphere composite solder was placed between the base material microcrystalline glass and the C / C composite material to be connected, and then placed in a brazing furnace at a vacuum degree of 5×10 -3 Pa, the temperature was raised to 770°C at a rate of 10°C / min, and the connection was brazed at 770°C for 10 min. After brazing, it was cooled to 200°C at a rate of 5°C / min, and finally the heating was turned off and the furnace was cooled to room temperature.

[0070] The size of the microcrystalline glass is 7mm×7mm×7mm, and the size of the C / C composite material is 7mm×7mm×7mmm; before brazing, the surfaces of the microcrystalline glass and the C / C composite material to be welded are polished with 240#, 400#, 600# and 1000# sandpaper in turn, then placed in acetone for ultrasonic cleaning for 10 minutes, and taken out to dry.

[0071] Comparative Example 1: The method for brazing dissimilar materials is carried out according to the following steps:

[0072] AgCuInTi solder powder is mixed into solder paste with anhydrous ethanol, and the solder paste is applied between the C / C composite material and the microcrystalline glass for soldering connection;

[0073] Before brazing, the surfaces of the glass-ceramics and C / C composite materials to be welded were polished with 240#, 400#, 600# and 1000# sandpapers in sequence, then ultrasonically cleaned in acetone for 10 minutes, and then taken out to dry;

[0074] The brazing process parameters are as follows: the vacuum brazing furnace is evacuated to a vacuum degree of 5×10 -3 Pa, then heated to 770℃ at a heating rate of 10℃ / min, and brazed at 770℃ for 10min. After brazing, cooled to 200℃ at a cooling rate of 5℃ / min, and finally turned off the heating and cooled to room temperature with the furnace.

[0075] Figure 2 The interface structure morphology of the hollow glass microsphere composite solder brazing joint in Example 1 is shown. Figure 3 The interface structure morphology of the direct brazing joint without glass microspheres in Comparative Example 1 is shown; Figure 2-3 As shown, after adding hollow glass microspheres in Example 1, the Ti-Cu phase in the joint interface is significantly reduced, and the shear strength of the joint reaches 10 MPa, which is 150% higher than that without adding glass microspheres.

[0076] Example 2: A method for brazing dissimilar materials based on hollow glass microsphere composite solder is carried out according to the following steps:

[0077] Step S1:

[0078] 5 g of hollow glass microspheres were dispersed in 1000 mL of deionized water, and ultrasonically cleaned at 25°C for 1 h. After ultrasonic cleaning, the mixture was allowed to stand for 3 h to remove the broken glass microspheres, and the upper floating material was taken to obtain hollow glass microspheres with complete structures.

[0079] The diameter of the hollow glass microspheres is 30 μm;

[0080] Step S2:

[0081] The hollow glass microspheres with complete structures obtained in step S1 are placed in a vacuum drying oven and dried for 10 hours at a vacuum degree of 10 Pa and a temperature of 80° C. to obtain dried hollow glass microspheres;

[0082] Step S3:

[0083] The dried hollow glass microspheres obtained in step S2 are mixed with solder powder, and then anhydrous ethanol as a dispersant is added, and mechanically stirred at a stirring speed of 100 r / min for 20 min to obtain a hollow glass microsphere composite solder;

[0084] The mass ratio of the dried hollow glass microspheres to the solder powder is 0.01:1, and the solder powder is AgCuInTi solder;

[0085] Step S4:

[0086] The hollow glass microsphere composite solder was placed between the base material microcrystalline glass and the C / C composite material to be connected, and then placed in a brazing furnace at a vacuum degree of 5×10 -3 Pa, the temperature was raised to 770°C at a rate of 10°C / min, and the connection was brazed at 770°C for 10 min. After brazing, it was cooled to 200°C at a rate of 5°C / min, and finally the heating was turned off and the furnace was cooled to room temperature.

[0087] The size of the microcrystalline glass is 7mm×7mm×7mm, and the size of the C / C composite material is 7mm×7mm×7mmm; before brazing, the surfaces of the microcrystalline glass and the C / C composite material to be welded are polished with 240#, 400#, 600# and 1000# sandpaper in turn, then placed in acetone for ultrasonic cleaning for 10 minutes, and taken out to dry.

[0088] Figure 4 The interface structure morphology of the hollow glass microsphere composite solder brazing joint in Example 2 is shown; Figure 2 , Figure 3and Figure 4 It can be seen from the comparison that with the increase of the content of hollow glass microspheres in the composite solder, the Ti-Cu phase in the joint interface is significantly reduced, there is almost no agglomeration of brittle compounds, and the final joint shear strength reaches 23MPa, which is 400% higher than that without adding glass microspheres.

Claims

1. A method for preparing a hollow glass microsphere composite solder, characterized in that The preparation method is carried out according to the following steps: Step S1: The hollow glass microspheres are dispersed in deionized water, and ultrasonically cleaned at 20-30° C. After the ultrasonic cleaning, the hollow glass microspheres are allowed to stand to remove the precipitate, and the upper floating matter is taken to obtain the hollow glass microspheres with complete structure; Step S2: The hollow glass microspheres with complete structures obtained in step S1 are placed in a vacuum drying oven for drying to obtain dried hollow glass microspheres; Step S3: The dried hollow glass microspheres obtained in step S2 are mixed with solder powder, and then a dispersant is added. After mixing evenly, a hollow glass microsphere composite solder is obtained; the mass ratio of the dried hollow glass microspheres to the solder powder is (0.001-0.05):

1.

2. The method for preparing a hollow glass microsphere composite solder according to claim 1, characterized in that In step S1, the ratio of the mass of the hollow glass microspheres to the volume of deionized water is (5-15) g: (600-1000) mL, and the diameter of the hollow glass microspheres is 2 μm-100 μm.

3. The method for preparing a hollow glass microsphere composite solder according to claim 1, characterized in that In step S1, the ultrasonic cleaning time is 0.5 to 12 hours, and the standing time is 1 to 3 hours.

4. The method for preparing a hollow glass microsphere composite solder according to claim 1, characterized in that During drying in step S2, the vacuum degree in the vacuum drying oven is 1Pa to 100Pa, the drying temperature is 60 to 100°C, and the drying time is 5 to 12h.

5. The method for preparing a hollow glass microsphere composite solder according to claim 1, characterized in that The solder powder described in step S3 is Cu-based solder, Ag-based solder, Ni-based solder, Sn-based solder, Ti-based solder or Zr-based solder.

6. The method for preparing a hollow glass microsphere composite solder according to claim 1, characterized in that The dispersant described in step S3 is anhydrous ethanol, acetone, ethylene glycol, cellulose solution or isopropanol.

7. The method for preparing a hollow glass microsphere composite solder according to claim 1, characterized in that In step S3, mechanical stirring is used for mixing, with a stirring speed of 10 to 500 r / min and a stirring time of 1 to 30 min.

8. A method for brazing dissimilar materials using a hollow glass microsphere composite solder prepared by the method described in any one of claims 1 to 7, characterized in that The method proceeds as follows: The hollow glass microsphere composite solder is placed between the surfaces of two dissimilar base materials to be welded for assembly, and then placed in a brazing furnace under a vacuum degree of 1×10 -4 ~5×10 -3 Pa, the temperature is raised to 20-150°C higher than the melting point of the brazing material, and the brazing connection is performed for 1-60 minutes. After the brazing is completed, it is first cooled to 200-450°C, and then cooled to room temperature, completing the brazing of dissimilar materials based on the hollow glass microsphere composite brazing material; The dissimilar base materials to be welded are C / C composite materials, SiO 2f / SiO2 composites, C / SiC composites, multiphase ceramics, oxide ceramics, glass-ceramics, sapphire, Ni-based alloys, Ti alloys, Zr alloys, Nb alloys and two of the Fe-based alloys.

9. The method for brazing dissimilar materials based on hollow glass microsphere composite solder according to claim 8, characterized in that The heterogeneous parent materials to be welded are glass-ceramics and C / C composite materials.

10. The method for brazing dissimilar materials based on hollow glass microsphere composite solder according to claim 8, characterized in that The heating rate is 1-30°C / min, and the cooling rate is 1-50°C / min.

Citation Information

Patent Citations

  • Ceramic hollow sphere multi-layer brazed diamond block and manufacturing method thereof

    CN103395009A

  • Method for cleaning silver-based solder

    CN109365383A

  • Grinding wheel for ceramic tile processing

    CN111136591A

  • Brazing filler metal system for air atmosphere brazing of YSZ ceramics and brazing method

    CN111644739A

  • Glass solder for producing building vacuum glass plate

    CN1907896A

Cited By

  • Brazing method for C / C composite material and glass material based on Ti-Cu composite modified layer and low-temperature glass brazing filler metal

    CN121405495A